Photon-upconverters for blue organic light-emitting diodes: a low-cost, sky-blue example. Issue 5 (14th February 2022) - Yang, Le; Chua, Xian Wei; Yang, Zhihong; Ding, Xiangpeng; Yu, Yong; Suwardi, Ady; Zhao, Meng; Ke, Karen Lin; Ehrler, Bruno; Di, Dawei
Abstract : We advocate triplet–triplet annihilation upconverters as candidates for blue FuLEDs (OLEDs enhanced by triplet-fusion), demonstrating here with the sky-blue DPBF. Its TTA or triplet-fusion behaviour is explored in both solutions and FuLED devices. Abstract : In the research ecosystem's quest towards having deployable organic light-emitting diodes with higher-energy emission ( e.g., blue light), we advocate focusing on fluorescent emitters, due to their relative stability and colour purity, and developing design strategies to significantly improve their efficiencies. We propose that all triplet–triplet annihilation upconversion (TTA-UC) emitters would make good candidates for triplet fusion-enhanced OLEDs ("FuLEDs"), due to the energetically uphill nature of the photophysical process, and their common requirements. We demonstrate this with the low-cost sky-blue 1, 3-diphenylisobenzofuran (DPBF). Having satisfied the criteria for TTA-UC, we show DPBF as a photon upconverter ( I th 92 mW cm −2 ), and henceforth demonstrate it as a bright emitter for FuLEDs. Notably, the devices achieved 6.5% external quantum efficiency (above the ∼5% threshold without triplet contribution), and triplet-exciton-fusion-generated fluorescence contributes up to 44% of the electroluminescence, as shown by transient measurements. Here, triplet fusion translates to a quantum yield ( Φ TTA-UC ) of 19%, at an electrical excitation of ∼0.01 mW cm −2 . The enhancement is meaningful for commercial blue OLED displays. We also found DPBF to have decent hole mobilities of ∼0.08 cm 2 V −1 s −1 . This additional finding can lead to DPBF being used in other capacities in various printable electronics.